TLOCOR MARINE TOURISM-LUSI ISLAND AS A MEANS OF ENVIRONMENTAL CONSERVATION AND EMPOWERMENT OF THE SURROUNDING COMMUNITY IN SIDOARJO - Pandu Rudy Widyatama; Muhajir Taslikhan; Nuril Huda (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
Tlocor Marine Tourism-Lusi Island, located in Sidoarjo, East Java, is an ecotourism destination that combines environmental conservation and local community empowerment. This study aims to analyze the role of tourism in the context of environmental conservation and empowerment of the surrounding community. The data were collected through field observations, interviews with five main informants (tourism coordinators, POKDARWIS members, and local communities), and documentation. In addition, numerical data were also added, including visitor information, community participation levels, economic influence, and environmental benefits to strengthen the analysis. The results of the study show that the Mangrove ecosystem is well maintained, functioning as a tourist attraction as well as a buffer for the coastal ecosystem. However, inadequate transportation access, lack of digital promotion, and low community participation are the main challenges. Nevertheless, the existence of this tourism has increased environmental awareness and created economic opportunities for the local community. With infrastructure support, better promotion, and optimal community involvement, Tlocor Marine Tourism-Lusi Island has great potential to develop into a leading ecotourism destination. Finally, this study emphasizes the importance of collaborative efforts between environmental conservation and community empowerment in sustainable ecotourism management.